THE SKETCHES OF MINANGKABAU SOCIETY IN NUR ST. ISKANDAR’S AND HAMKA’S NOVELS - Yasnur Asri (Humaniora, 2014)
This study aims to describe the sketches of Minangkabau society before independence as reflected in Nur St. Iskandar’s and Hamka’s novels. In Iskandar’s novel, a good character in society is a Western educated person who is an employer at the Dutch office. In Hamka’s novel, a good character of society is one holding religious (Islam) education and working as an entrepreneur. Both characters reflect a social group who tends to demonstrate rationality and good attitude, but opposes any tradition that contradicts religion (Islam). The life sketches reflected in Nur St. Iskandar’s and Hamka’s novels also have impacts on the Minangkabau societies’ way of thinking.